GIS-based and Geospatial analysis: mapping and visualizing the trend of Covid-19 data in selected Asian countries - Jiun, Guan Wong; Min, Jun Lim; Siok, Kun Sek; Khang, Yi Sim (Penerbit Universiti Kebangsaan Malaysia, 2024)
The outbreak of COVID-19 has caused many losses, unprecedented threats, and a change of life in many ways. The daily records of cases and other related data contain important information to reflect the severity, trend, and risk level of each country over time. Thus, this study aims to examine the trend, severity, and change of the pandemic situation in Asia over four periods. In this study, the data are collected from 48 Asian countries. The four periods are selected to represent different stages of the outbreak based on the daily records for comparison. The four periods are 6th January 2020, 6th January 2021, 6th July 2021, and 6th June 2022. The data include the daily record of confirmed cases, the number of deaths, the number of vaccinations, and the number of recoveries. Besides, this study also examines the accumulated cases up to 6th July 2022. The accumulated data includes the four data points mentioned and the severity index. The Local Indicators of Spatial Association (LISA) is applied to detect the clustering pattern and hotspot area as well as the existence of spatial effects in the data. The GIS mapping reveals that China has the most severe situation in Period 1. Nevertheless, from Periods 2 to 3, the pandemic is spreading speedily and widely over the Asian region. The deadly situation (confirmed cases, high fatality, and vaccination) is centred around Southeast Asia and West Asia. Nonetheless, with the exception of China, the situation is improving in Period 4.